Absence of Behavioral Harm Following Non-efficacious Sexual Orientation Change Efforts: A Retrospective Study of United States Sexual Minority Adults, 2016–2018 - Sullins, D. Paul (Frontiers in Psychology, 2022)
Background: Do sexual minority persons who have undergone unsuccessful sexual orientation change efforts (SOCE) suffer subsequent psychological or social harm from the attempt? Previous studies have conflated present and past, even pre-SOCE, harm in addressing this question. This study attempts, for the first time, to isolate and examine the question of current psychosocial harm for former SOCE participants among sexual minorities in representative population data. Method: Using nationally representative data (n = 1,518) across three cohorts of sexual minorities (centered in 1969, 1987, and 2003) in the United States, persons exposed to SOCE were compared with the remainder not exposed to SOCE on two measures of internal distress—psychological distress (Kessler scale) and current mental health—and seven measures of behavioral harm: substance abuse (DUDIT); alcohol dependence (AUDIT-C); self-harm; suicide ideation; suicide planning; suicide intentions; and suicide attempts. Results: The SOCE group was statistically indistinguishable from the non-SOCE group on any measure of harm. For behavioral harm, risk ratios were .97-1.02. Harm was equivalent for the two groups despite the SOCE group having experienced higher lifetime and current minority stress, greater childhood adversity, and lower socioeconomic status. Logistic regression models that adjusted for these differences suggest that SOCE exposure reduced the effect of minority stress and childhood adversity for suicide attempts, although this effect did not fully account for the equivalence between the SOCE and non-SOCE groups. Conclusion: Despite higher exposure to factors predicting behavioral harm—minority stress, childhood adversity and lower socioeconomic background—sexual minority persons who had undergone failed SOCE therapy did not suffer higher psychological or social harm. Concerns to restrict or ban SOCE due to elevated harm are unfounded. Further study is needed to clarify the reasons for the absence of harm from SOCE.